(untitled) (Tribhuvan University Journal of Microbiology, 2018)
Objectives: The study was done with an aim to determine the gain and loss of functions among the actinomycetes mutants induced by sodium azide. Methods: The study was carried out in the laboratory of the Sainik Awasiya Mahavidhayala, Bhaktapur, Nepal from 2016 December to 2017 March. A total of 30 soil samples were collected from Tokha, Bhaktapur area and Godawari area. Actinomycetes were isolated from the soil sample using pour plate technique on selective media; starch casein agar. The isolates were identified by using standard microbiological methods and each isolate was exposed to different concentration of sodium azide to generate mutants. The wild type and mutants were compared in morphology, biochemical reactions and antibiotic susceptibility to test organism to determine the gain and loss of functions. Results: Among 30 samples processed, 20(67%) actinomycetes were isolated, in which 6 (20%) were identified as the Streptomyces spp. A total of 28 mutants were isolated from 6 wild types by exposed at 10ppm, 20ppm, 40ppm, 50ppm, 100ppm concentration of sodium azide. Out of 28 mutants formed, only 10 mutants from sample showed same pigmentation as its wild type while other 18 mutants showed change in their pigmentation. In sugar utilization test, 8 different sugars for 28 mutants each, 56 cases showed Gain of Function (GOF), similarly 44 cases showed Loss of function (LOF). Antibiosis remained unaffected against Pseudomonas i.e. no GOF or LOF was seen. Only 2 cases of LOF against Staphylococcus aureus were seen while there were no cases of LOF in other pathogens. 3 cases of GOF against E. coli, 4 against S Typhi and 4 against S. aureus were observed. Conclusion: The potential of mutant actinomycetes has been realized, and hence opens exciting avenues in the field of biotechnology and biomedical research.